Thirteen nodule-specific or nodule-enhanced genes encoding products homologous to cysteine cluster proteins or plant lipid transfer proteins are identified in Astragalus sinicus L. by suppressive subtractive hybridization - Chou, Min-Xia (Journal of experimental botany, 2006)
Thirteen nodule-specific or nodule-enhanced genes have been revealed by suppressive subtractive hybridization (SSH) with two mRNA populations of infected and uninfected control roots of Astragalus sinicus. Eleven of them encode small polypeptides showing homology to cysteine cluster proteins (CCPs) that contain a putative signal peptide and conserved cysteine residues. Among these CCP-like genes, AsG257 codes for a homologue of the defensin 2 family and AsD255 contains a scorpion toxin-like domain at the C-terminus. Sequence analysis of a genomic AsD255 fragment which was isolated revealed that one intron separates the first exon encoding the signal peptide from the second exon encoding the cysteine cluster domain of this nodulin. Another two genes, AsE246 and AsIB259, encode two different products similar to lipid transfer proteins (LTPs). Virtual northern blot and reverse transcription-polymerase chain reaction (RT-PCR) analysis indicated that the other genes except AsIB259 and AsC2411 were expressed exclusively in inoculated roots and that their expression was 2-4 d later than that of the leghaemoglobin (Lb) gene during nodule development. Transcription of AsIB259 was also detected in uninfected control roots but with a significant decline in expression and a temporal expression similar to Lb. AsC2411 had a basal expression in control roots identified by RT-PCR. Sequence alignment showed that the putative proteins AsE246 and AsIB259 show lower homology with LTPs from legumes than with those from other plants